2021
DOI: 10.1051/shsconf/20219201014
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and its impact on Slovak economy during corona crisis

Abstract: Research background: The presented article analysis major impacts of corona crisis on global and subsequently Slovak economy. It divides major impacts into several basic categories. These categories are presented in the methods part of the article. First of all, we analyze and discuss economic impacts, subsequently shocks in supply and demand and at last impacts of policies. These categories contain wide literature research in order to offer complex overview of the topic. The results and discussion part offers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The development of the unemployment rate in Slovakia (7.4% at the end of second-quarter 2020) was also addressed by Hlawiczka and Kollar (2021). They analysed several macroeconomic indicators during the corona crisis, where it was found that the Slovak labour market looks worse than in neighbouring euro area countries (7.1% to the second quarter of 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The development of the unemployment rate in Slovakia (7.4% at the end of second-quarter 2020) was also addressed by Hlawiczka and Kollar (2021). They analysed several macroeconomic indicators during the corona crisis, where it was found that the Slovak labour market looks worse than in neighbouring euro area countries (7.1% to the second quarter of 2020).…”
Section: Discussionmentioning
confidence: 99%